2017
DOI: 10.4046/trd.2017.80.1.83
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Autophagy on the Cigarette Smoke Extract-Induced Apoptosis of Bronchial Epithelial Cells

Abstract: BackgroundPrevious studies report that apoptosis and autophagy are involved in the pathogenesis of emphysema, and macroautophagy is one of the processes regulating the apoptosis pathway. However, few studies have evaluated whether chaperone-mediated autophagy (CMA) contributes to the regulation of apoptosis. In this study, we investigated the impact of autophagy, including both macroautophagy and CMA, on the apoptosis in bronchial epithelial cells.MethodsCigarette smoke extract (CSE) was injected intratracheal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
4
14
0
Order By: Relevance
“…Previous studies have revealed that CSE exposure can induce apoptosis, trigger ERS, UPR, and autophagy, and eventually results in the apoptosis of pulmonary cells under certain circumstances (30)(31)(32). A recent study also showed that CSE induces apoptosis, macroautophagy, and chaperone-mediated autophagy of bronchial epithelial cells (33). In line with this, our results showed that CSE treatment induced apoptosis, autophagy, and expression of ERS-related proteins in HBE cells.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have revealed that CSE exposure can induce apoptosis, trigger ERS, UPR, and autophagy, and eventually results in the apoptosis of pulmonary cells under certain circumstances (30)(31)(32). A recent study also showed that CSE induces apoptosis, macroautophagy, and chaperone-mediated autophagy of bronchial epithelial cells (33). In line with this, our results showed that CSE treatment induced apoptosis, autophagy, and expression of ERS-related proteins in HBE cells.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that the decrease in cell viability due to CS exposure is related to apoptosis and autophagy . So, we investigated the activation of apoptosis and autophagy.…”
Section: Discussionmentioning
confidence: 97%
“…However, excessive ERS can lead to programmed cell death through an ERS-associated apoptosis pathway and activation of Caspase 12 in rodents (Caspase 4 in human) (Kaufman, 2002; Ron, 2002; Ron and Walter, 2007). Several studies have reported CSE-induced apoptosis in vitro , especially ERS associated cell apoptosis (Lee et al, 2017a; Lee et al, 2017b; Jiao et al, 2017; Song et al, 2017; Iu et al, 2017). This process involves UPR signaling pathways activation, induced via ER transmembrane molecules, including PERK, IRE1 and ATF6, and sequence different signaling pathways, final activating ERS-associated apoptosis (Tokunaga et al, 2010; Gan et al, 2011; Tagawa et al, 2011; Yuan et al, 2012; Kitaguchi et al, 2012; Kelsen, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 90% of COPD cases are caused by cigarette smoke (Martinez and Han, 2012). Cigarette smoke (CS) induces an imbalance of cell proliferation and apoptosis, which is thought to be critical in the pathogenesis of COPD, and determine disease phenotype (Haw et al, 2016; Bodas et al, 2016; Lee et al, 2017a; Lee et al, 2017b). The three classical apoptotic pathways: endoplasmic reticulum stress (ERS), intrinsic, and extrinsic apoptotic pathways all have been implicated in the pathogenesis of COPD (Wu et al, 2015; Fujita et al, 2016; Yuan et al, 2017; Lin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%